57Co-Hematoporphyrin Accumulation by Experimental Tumors - Anghileri, L. J.; Heidbreder, M.; Mathes, R. (Nuklearmedizin - NuclearMedicine, 1976)
The in vivo distribution of 57Co-hematoporphyrin in adenocarcinoma BW10232-bearing mice has been studied. Tumor-bearing and normal animals exhibit similar patterns of radioactivity accumulation. Twenty-four hours after the administration of the radiocompound the ratios tumor to blood and tumor to muscle indicate a potential value of this radioactive porphyrin for the detection of some types of tumor.